A Double‐Hurdle Analysis of Demand for Powdered Milk: Evidence from Household Survey Data in an Urban Chinese Province. Issue 3 (3rd February 2014) - Wu, Beibei; Chen, Yongfu; Si, Wei; Chien, Hsiaoping
ABSTRACT The objective of this study is to explore the determinants of urban at‐home consumption demand for powdered milk in Guangdong province from 2007 to 2009. A double‐hurdle model is used in this analysis based on survey data. The data include 8188 household distributed in 15 cities and prefectures of Guangdong province. Major findings show that the income growth of urban household, an increase in the level of education of the householder, and the different age groups within the household all have positive effects on urban at‐home consumption demand for powdered milk. The prices of powdered milk have negative effects on milk consumption. Families in the Pearl River Delta consume more powdered milk than families in the other regions. The powdered milk consumption has not been significantly affected by the 2008 Chinese melamine tainted milk scandal.